Implementing Splunk 7, Third Edition : Effective operational intelligence to transform machine-generated data into valuable business insight, 3rd Edition. - D. Miller, James (Packt Publishing, 2018)
This book will help you implement Splunk 7's new services and will show you how to utilize them to quickly and efficiently process machine-generated big data. You will explore Splunk Cloud and the Machine Learning Toolkit and use them with ease throughout your organization. By the end of the book, you will have learned to implement these ...